PENGEMBANGAN BAHAN AJAR UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA KELAS VII SMP NEGERI 1 TALAWI TAHUN PELAJARAN 2013-2014 - Herty Arnita Sinaga (JURNAL TEMATIK, 2015)
This study aims to: (1) generate a decent textbook to use, easy to learn and can be used for learners individual learning, (2) to determine the effectiveness of the developed textbooks on the subjects of Indonesian. This research is the development of a research model product development Borg and Gall combined with a model of Dick and Carey instructional design. The research method consisted of two phases, phase I trial of the product is comprised of: (1) validation of subject matter experts, (2) validation of expert instructional design, (3) individual trial, (4 ) small group testing, and (5) limited field trials; Phase II is a test of the effectiveness of the product by: (1) to test the normality of data research, (2) to test the homogeneity of the study data, (3) test the hypothesis of the study and (4) calculate efektiivtas textbook developed. The end product of the development of this teaching material continues to test the effectiveness of the product. The study was conducted on secondary school students of class VII SMP Negeri 1 Talawi. The method used in this study is quasi-experimental methods. Study sample as many as 802 students consisting of 40 students as the experimental class taught using teaching material and 40 other students as a control class using the textbook as that goes far in the learning process. The test results proved the hypothesis that there are significant differences between student learning outcomes learn using teaching material with student learning outcomes to learn using textbooks. This is indicated by the value processing obtained = 8,8 > = 1,6689, with dk = (n1 + n2 -2) at significance level α = 0,05. It was concluded that the learning outcomes of students using teaching material learn by 96,8% higher than the group of students using the textbook learn of 81,1%.